(untitled) (Journal of Health, Population and Nutrition, 2011)
Nutrition and health are fundamental pillars of human development across the entire life-span. The potential role of non-timber forest products (NTFPs) in improving nutrition and health and reduction of poverty has been recognized in recent years. NTFPs continue to be an important source of household food security, nutrition, and health. Despite their significant contribution to food security, nutrition, and sustainable livelihoods, these tend to be overlooked by policy-makers. NTFPs have not been accorded adequate attention in development planning and in nutrition-improvement programmes in Ghana. Using exploratory and participatory research methods, this study identified the potentials of NTFPs in improving nutrition and food security in the country. Data collected from the survey were analyzed using the SPSS software (version 16.0). Pearson’s correlation (p<0.05) showed that a significant association exists between NTFPs and household food security, nutrition, and income among the populations of Bibiani-Bekwai and Sefwi Wiawso districts in the western region of Ghana. NTFPs contributed significantly to nutrition and health of the poor in the two districts, especially during the lean seasons. The results of the survey also indicated that 90% of the sampled population used plant medicine to cure various ailments, including malaria, typhoid, fever, diarrhoea, arthritis, rheumatism, and snake-bite. However, a number of factors, including policy vacuum, increased overharvesting of NTFPs, destruction of natural habitats, bushfires, poor farming practices, population growth, and market demand, are hindering the use and development of NTFPs in Ghana. The study also provides relevant information that policy-makers and development actors require for improving nutrition and health in Ghana. Key words: Forest; Food security; Health; Nutrition disorders; Micronutrients; Non-timber forest products; Nutrition; Plant medicine; Poverty alleviation; Ghana DOI: http://dx.doi.org/10.3329/jhpn.v29i2.7856 J HEALTH POPUL NUTR 2011 Apr;29(2):141-148